Risk factors for atherosclerosis in black South African patients on Haemodialysis - Amira, Christiana Oluwatoyin (My University, 2006)
ABSTRACT INTRODUCTION The risk of cardiovascular disease in patients with end stage renal disease (ESRD) is far greater than in the general population. Amongst patients with ESRD, the prevalence of coronary artery disease (CAD) and congestive heart failure is approximately 40% compared with 5-12% in the general population. The excess risk is caused by multiple traditional and non-traditional risk factors for ischaemic heart disease present in these patients. There is little information on CAD and its risk factors in black haemodialysis patients as most of these studies were carried out in the white population. This study is therefore aimed at determining the risk factors for atherosclerosis in Black and non-black (White and Indian) South African patients on haemodialysis. METHODS Fifty-eight black patients and twenty-six non-black patients on haemodialysis were recruited. Sixty-three age and sex matched controls (staff, students and kidney donors) were also recruited. Fasting venous blood samples were drawn for measurement of Creactive protein, homocysteine, Lp (a), serum lipids and adiponectin. Carotid intima-media thickness and plaque occurrence was measured by B-mode ultrasonography. Echocardiography was used to determine LVH. vi RESULTS Haemodialysis (HD) patients had significantly lower total cholesterol, LDL cholesterol and triglycerides compared with controls (p<0.001; p= 0.042). Hs-CRP, adiponectin and homocysteine levels were significantly higher in patients compared with controls (p< 0.001). The prevalence of plaques was significantly higher among HD patients (32%) compared with controls (7%) X2 = 60.72 p< 0.001. LVMI was significantly higher among HD patients (194.25± 7.69gm/m2) compared with controls (93.21 ± 3.27 gm/m2) p < 0.001. No significant difference between patients (Black or Asian/White) and controls with respect to CIMT was found. CVD risk factors in black haemodialysis patients and black controls showed a similar pattern to the whole study population combined. Risk factors associated with CIMT on regression analysis were total cholesterol, LDL-cholesterol, age, Hs-CRP, family history of CKD. Risk factors associated with plaque occurrence on logistic regression analysis were age, systolic blood pressure, male gender, smoking, calcium phosphate product and serum phosphate. CONCLUSION HD patients have a high prevalence of traditional and non-traditional risk factors for atherosclerosis and this is independent of race. Traditional risk factors like lipids were much lower in ESRD patients. HD patients showed a high prevalence of atherosclerosis as measured by increased carotid intima-media thickness and plaque occurrence in carotid arteries. Hs-CRP correlated significantly with a surrogate marker of atherosclerosis (CIMT).
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg, 2005
Keywords: cardiovascular disease; renal disease; heart failure; Echocardiography